Trio Marmalade and Hominy Grits: Gullah Traditions and Home Cooking in Ntozake Shange’s Sassafrass, Cypress, and Indigo - Mookerjee, Rita (FRAME, Journal of Literary Studies, 2026)
Sassafrass, Cypress, and Indigo is a novel that focuses on an understudied community in the American South. Ntozake Shange uses food history, recipes, and rituals to acquaint readers with Gullah people. Works of fiction about the Gullah people remain limited within African American literature, but this coastal community is alive and well. In Black Hunger: Soul Food and America, Doris dubs Sassafrass, Cypress, and Indigo a “recipistolary novel” (Witt 11). This notion of recipistolary is what makes the novel unique within the dynamic realm of Black American literature. Historically, Black women have been excluded from consideration in the culinary arts. By contrast, Sassafrass, Cypress, and Indigo centers Gullah women in Black feminist writing while preserving traditions and tropes that are unique to the Lowland South and daily Black life in the United States. Shange passed away in 2018, and so this study punctuates her legacy as a Black storyteller with food, women, and history in mind.